2015
DOI: 10.3168/jds.2014-9136
|View full text |Cite
|
Sign up to set email alerts
|

Ketonemia in dairy goats: Effect of dry period length and effect on lying behavior

Abstract: In dairy animals, a successful transition from one lactation to the next includes minimizing negative energy balance. Cows experiencing excessive negative energy balance typically develop metabolic complications following parturition (e.g., ketosis); does are also susceptible before kidding (e.g., pregnancy toxemia). It is not known to what extent the provision and the length of the dry period affect these conditions in does. Furthermore, whereas clinical symptoms of these conditions include lethargy, behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 38 publications
1
8
1
1
Order By: Relevance
“…Dairy cows with subclinical ketosis are 20–50% less likely to become pregnant at first AI than normal cows (Walsh et al 2007) and show greater lethargy and lying times (Itle et al 2015). Similar effects have been reported in dairy goats (Zobel et al 2015). There is also considerable variation between animals in what is ‘normal’.…”
Section: Dairy Animal Wellbeing and The Welfare Quality® Programmesupporting
confidence: 87%
“…Dairy cows with subclinical ketosis are 20–50% less likely to become pregnant at first AI than normal cows (Walsh et al 2007) and show greater lethargy and lying times (Itle et al 2015). Similar effects have been reported in dairy goats (Zobel et al 2015). There is also considerable variation between animals in what is ‘normal’.…”
Section: Dairy Animal Wellbeing and The Welfare Quality® Programmesupporting
confidence: 87%
“…In the present study, an overall LT of 11.78 ± 1.47 h/d (mean ± SD) was examined. This is lower than in studies of Zobel et al [ 19 , 22 ], who found a mean lying time of healthy goats of 15.45 h/d two to 12 days before and after kidding [ 22 ] and 14.5 h/d in late gestation goats [ 19 ]. In a study of Patt et al [ 23 ], the mean LT of non-lactating horned goats was 13.22 h/d (in groups of seven goats/group).…”
Section: Discussioncontrasting
confidence: 57%
“…Pathological levels of β-OHB are observed in situations associated with metabolic challenge. Dairy goats with ketonemia show reduced milk production before and after giving birth [33]. Similarly, Chios dairy ewes with high levels of β-OHB and NEFA before and after parturition show lower milk yield during lactation [16].…”
Section: Discussionmentioning
confidence: 99%
“…BCS in the peripartum period and DPL also affect milk yield and are associated with metabolic disorders [16,33,40]. A DPL shorter than 30 days and longer than 91–120 days reduced milk production in Lacaune dairy ewes [18].…”
Section: Discussionmentioning
confidence: 99%